Lithium iron phosphate carbon-coated material, preparation method thereof and battery
By coating the carbon layer twice, the shortcomings of lithium iron phosphate material in compaction density and cycle stability were solved, and its electrochemical properties were significantly improved.
Patent Information
- Application Number
- CN202411673228.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-18
AI Technical Summary
The existing lithium iron phosphate materials have shortcomings in compaction density and cycle stability, which affects their electrochemical properties.
Lithium iron phosphate carbon coated material is prepared by a method of twice coated carbon layer. The specific steps include mixing the lithium source, phosphorus source, iron source with a solid carbon source, grinding, drying, sintering, crushing, performing the first coat, and then grinding and acetylene secondary sintering to form the second coat. Carbon layer.
This method improves the electronic conductivity, interface corrosion resistance and lithium ion diffusion ability of the material by forming a uniform thin carbon shell on the surface of lithium iron phosphate crystals, improves the circulation performance, and improves the compaction density of the material.
Smart Images

Figure CN119481007A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of energy materials, and in particular relates to a lithium iron phosphate carbon-coated material and a preparation method thereof, and a battery. Background Art
[0002] Surface carbon coating is a common treatment method to improve material compaction, which can promote the insertion and extraction rate of lithium ions in electrode materials, improve conductivity, inhibit particle size growth, and improve the chemical stability of LiFePO4. In-depth research on the surface properties of LiFePO4 and carbon coating will guide the optimization of carbon coating layers and the effective synthesis of uniform carbon-coated LiFePO4.
[0003] At present, the commonly used carbon sources in industry include organic carbon sources such as sucrose, glucose, PEG and citric acid. However, the effect of carbon sources on the electrochemical properties of LiFePO4 / C composite materials is very complex, and the effects of different carbon sources are also different. Due to different coating methods, synthesis processes, etc., the effects on the electrochemical properties of LiFePO4 / C composite materials are also different. In addition, LiFePO4 / C with high compaction density is very important for practical applications. Summary of the invention
[0004] The present application provides a method for high-density carbon coating of lithium iron phosphate, which aims to solve the problems of compaction density and cycle stability of lithium iron phosphate to a certain extent.
[0005] In a first aspect, the present application provides a method for preparing a lithium iron phosphate carbon-coated material, comprising the following steps:
[0006] S1, mixing a lithium source, a phosphorus source, an iron source and a solid carbon source, and adding water to prepare a first mixed slurry;
[0007] S2, grinding the first mixed slurry to obtain a second mixed slurry;
[0008] S3, drying, sintering, cooling, and crushing the second mixed slurry to obtain a primary coated lithium iron phosphate powder;
[0009] S4, grinding the primary coated lithium iron phosphate powder, introducing acetylene for secondary sintering, and cooling to obtain a secondary coated lithium iron phosphate carbon-coated material.
[0010] By coating the carbon layer twice, a uniform thin shell is formed on the surface of the lithium iron phosphate crystal, which can minimize the direct contact between the lithium iron phosphate crystal surface and the electrolyte, reduce the dissolution of Fe ions, and improve the electronic conductivity of the material; the coated carbon layer can also improve the interface corrosion resistance and promote the interface lithium ion diffusion, thereby improving the interface lithium ion transmission and interface side reaction problems of lithium iron phosphate materials in the existing technology and improving the cycle performance; the formed carbon layer can also inhibit crystal growth and effectively improve the compaction density of the material.
[0011] Through the method of solid carbon source + vapor deposition, the surface carbon content of lithium iron phosphate is increased, the conductivity of the material is improved, and excessive particle growth is inhibited.
[0012] In a second aspect, the present application provides a lithium iron phosphate carbon-coated material prepared by the method of the first aspect.
[0013] In a third aspect, a battery comprises the lithium iron phosphate carbon-coated material prepared by the method of the first aspect, or the lithium iron phosphate carbon-coated material of the second aspect.
[0014] It can be understood that the beneficial effects of the second to third aspects mentioned above can be found in the relevant description of the first aspect mentioned above, and will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0016] Figure 1 It is a test diagram of the cycle performance effect of the embodiment of this scheme and the comparative example. DETAILED DESCRIPTION
[0017] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0018] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0019] In the present application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, a~b (i.e. a and b), a~c, b~c, or a~b~c, where a, b, c can be single or multiple, respectively.
[0020] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. For example, without departing from the scope of the implementation regulations of this application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0021] The terms used in the embodiments of the present application are only for the purpose of describing specific implementation rules, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the implementation rules of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0022] It should be understood that in the various embodiments of the present application, the size of the serial number of each process does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the implementation regulations of this application.
[0023] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0024] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0025] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0026] In a first aspect, the present invention provides a method for preparing a lithium iron phosphate carbon-coated material, comprising the following steps:
[0027] S1, mixing a lithium source, a phosphorus source, an iron source and a primary carbon source, and adding water to prepare a first mixed slurry;
[0028] S2, grinding the first mixed slurry to obtain a second mixed slurry;
[0029] S3, drying, sintering, cooling, and crushing the second mixed slurry to obtain a primary coated lithium iron phosphate powder;
[0030] S4, grinding the primary coated lithium iron phosphate powder, introducing acetylene for secondary sintering, and cooling to obtain a secondary coated lithium iron phosphate carbon-coated material.
[0031] In some embodiments, the lithium source is a combination of one or more of lithium carbonate, lithium hydroxide, lithium oxalate, lithium acetate, lithium nitrate, lithium phosphate and lithium dihydrogen phosphate.
[0032] The phosphorus source is one or more of diammonium phosphate, sodium phosphate, potassium phosphate, triammonium phosphate, diammonium phosphate, diammonium hydrogen phosphate, iron phosphate, manganese phosphate, lithium phosphate, lithium dihydrogen phosphate or phosphoric acid.
[0033] The iron source is one or more of ferrous phosphate, ferrous oxide, ferrous sulfate, ferrous nitrate, ferric nitrate, ferrous chloride, ferric sulfate, ferric chloride, ferrous oxalate or ferric hydroxide.
[0034] The carbon source is a combination of one or more of PEG, glucose, sucrose, citric acid, maltose, cyclodextrin, fructose and graphene.
[0035] In some embodiments, the addition ratio of Li, P, Fe, and C in S1 is 1-1.1:1:1-1.1, and the solid content of the first mixed slurry is 20%-50%.
[0036] In some embodiments, the size of the zirconium beads used in the grinding in S2 is 0.4 μm, the grinding time is 30-180 min, and the D50 of the second mixed slurry is 0.4-0.5 μm.
[0037] In some embodiments, the sintering process in S3 is as follows: nitrogen is introduced throughout the process for protection, the sintering temperature is 750-850° C., the heating rate is 5-15° C. / min, and the insulation time is 8-12 hours.
[0038] In some embodiments, the secondary sintering process described in S4 is: in a rotary kiln, nitrogen is passed for 0-1h before heating, and nitrogen is passed throughout the sintering process for protection. After the temperature is raised to 750°C, acetylene is passed at a flow rate of 0-0.2L / min and kept warm for 0.5-1h.
[0039] In a second aspect, the present invention provides a lithium iron phosphate carbon-coated material prepared as in the first aspect.
[0040] In a third aspect, the present invention provides a battery, comprising the lithium iron phosphate carbon-coated material prepared by the first aspect, or the lithium iron phosphate carbon-coated material described in the second aspect.
[0041] The technical solution of the present application is illustrated below through specific embodiments and comparative examples.
[0042] In order to enable the above implementation details and operations of the present application to be clearly understood by those skilled in the art, and to significantly demonstrate the improved performance of the embodiments of the present application, the above technical solutions are illustrated by means of multiple embodiments below.
[0043] Embodiment 1:
[0044] A method for preparing a lithium iron phosphate carbon-coated material,
[0045] S1. A lithium source (lithium carbonate: battery grade, purity 99.5%), a phosphorus source, an iron source (ferric phosphate: Fe / P>0.965) and a primary carbon source (PEG: molecular weight 2000, glucose: main content>99.5%) are mixed in a certain proportion, Li, Fe, P, and C are mixed in a ratio of 1.03:1:1.03, and water is added to form a slurry with a solid content of 40% to 50%;
[0046] S2, grinding the slurry prepared in S1, using zirconium beads with a size of 0.4 μm, grinding for 100 to 300 min, and obtaining a slurry with a D50 of 0.4 to 0.5 μm;
[0047] S3, drying the slurry ground in S2 and then sintering; nitrogen is introduced throughout the sintering process for protection, the heating rate is 5-15°C / min, the insulation time is 8-10h, and the cooled powder is gas-crushed to obtain a primary coated lithium iron phosphate powder;
[0048] S4. Weigh a certain amount of powder obtained by sintering S3 and grind it briefly. Then transfer it to a rotary kiln. Pass nitrogen for 0.5h before heating. Pass nitrogen for protection during the entire sintering process. After heating to 750℃ at 10℃ / min, pass acetylene at a flux of 50ml / min. Keep warm for 1h and then cool naturally to obtain secondary coated lithium iron phosphate.
[0049] Embodiment 2:
[0050] A method for preparing a lithium iron phosphate carbon-coated material,
[0051] S1. A lithium source (lithium carbonate, specification: battery grade, purity 99.5%), a phosphorus source, an iron source (ferric phosphate, specification: Fe / P>0.965) and a primary carbon source (PEG: molecular weight 2000, glucose: main content>99.5%, specification) are mixed in a certain proportion, Li, Fe, P, and C are mixed in a ratio of 1.03:1:1.03, and water is added to form a slurry with a solid content of 40% to 50%;
[0052] S2, grinding the slurry prepared in S1, using zirconium beads with a size of 0.4 μm, grinding for 100 to 300 min, and obtaining a slurry with a D50 of 0.4 to 0.5 μm;
[0053] S3, drying the slurry ground in S2 and then sintering; nitrogen is introduced throughout the sintering process for protection, the heating rate is 5-15°C / min, the insulation time is 8-10h, and the cooled powder is gas-crushed to obtain a primary coated lithium iron phosphate powder;
[0054] S4. Weigh a certain amount of powder obtained by sintering S3 and grind it briefly. Then transfer it to a rotary kiln. Pass nitrogen for 0.5h before heating. Pass nitrogen for protection during the entire sintering process. After heating to 750℃ at 10℃ / min, pass acetylene at a flux of 100ml / min. Keep warm for 1h and then cool naturally to obtain secondary coated lithium iron phosphate.
[0055] Comparative Example 1:
[0056] The difference between this embodiment and embodiment 1 is that no secondary sintering and carbon coating treatment is performed.
[0057] A method for preparing a lithium iron phosphate carbon-coated material,
[0058] S1. A lithium source (lithium carbonate: battery grade, purity 99.5%), a phosphorus source, an iron source (ferric phosphate: Fe / P>0.965) and a primary carbon source (PEG: molecular weight 2000, glucose: main content>99.5%) are mixed in a certain proportion, Li, Fe, P, and C are mixed in a ratio of 1.03:1:1.03, and water is added to form a slurry with a solid content of 40% to 50%;
[0059] S2, grinding the slurry prepared in S1, using zirconium beads with a size of 0.4 μm, grinding for 100 to 300 min, and obtaining a slurry with a D50 of 0.4 to 0.5 μm;
[0060] S3, drying the slurry ground in S2 and then sintering; nitrogen is introduced throughout the sintering process for protection, the heating rate is 5-15°C / min, the insulation time is 8-10h, and the cooled powder is gas-crushed to obtain a primary coated lithium iron phosphate powder;
[0061] Comparative Example 2:
[0062] The difference between this embodiment and embodiment 1 is that the amount of carbon source added is different.
[0063] A method for preparing a lithium iron phosphate carbon-coated material, comprising: S1, mixing a lithium source (lithium carbonate: battery grade, purity 99.5%), a phosphorus source, an iron source (iron phosphate: Fe / P>0.965) and a primary carbon source (PEG: molecular weight 2000, glucose: main content>99.5%) in a certain proportion, adding Li, Fe, P and C in a ratio of 1.03:1:1.05, and adding water to form a slurry with a solid content of 40% to 50%;
[0064] S2, grinding the slurry prepared in S1, using zirconium beads with a size of 0.4 μm, grinding for 100 to 300 min, and obtaining a slurry with a D50 of 0.4 to 0.5 μm;
[0065] S3, drying the slurry ground in S2 and then sintering; nitrogen is introduced throughout the sintering process for protection, the heating rate is 5-15°C / min, the insulation time is 8-10h, and the cooled powder is gas-crushed to obtain a primary coated lithium iron phosphate powder;
[0066] Test example:
[0067] The performance tests of the embodiments and comparative examples are shown in Table 1 below. The difference in carbon content between the comparative example and the embodiments is about 0.1%, and the increase in the table is not large. However, the compaction density of the powder is greatly improved, and the powder resistance of the material is effectively reduced, indicating that the secondary carbon coating effectively modifies the powder material, can effectively improve the electrical conductivity of the material, and is beneficial to improving the electrochemical properties of the material.
[0068] Table 1: Performance tests of examples and comparative examples
[0069]
[0070] The button cells assembled with the powder materials of the comparative example and the embodiment as positive electrode materials were subjected to charge and discharge tests at different rates. The results are shown in the table. The 0.1C first discharge specific capacity of the embodiment and the comparative example is about 160mAh / g, and the difference in discharge capacity at 1C does not exceed 3.57%, indicating that the secondary carbon-coated powder material has a higher rate performance, and after 50 cycles, the capacity retention rate of the secondary carbon-coated powder is better, and it has a good application prospect. The specific data are shown in the following Tables 2 and 3:
[0071] Table 2: Example and comparative example charge and discharge test
[0072]
[0073] Table 3: Cyclic performance test of examples and comparative examples
[0074]
[0075] See the cycle performance test diagram for details. Figure 1 .
[0076] After secondary carbon coating with inorganic carbon source, the specific surface area of the material obtained in the embodiment is improved, the contact with the electrolyte is more complete, and the diffusion resistance can be effectively reduced; the powder resistance is reduced, and the internal resistance of the electrode after being prepared into a battery is reduced, which is beneficial to improving the electrochemical properties of the material; the powder compaction is increased, and a higher energy density can be achieved after processing; after 50 cycles of power-on and power-off, after capacity climbing, the capacity retention rate is high, and the capacity is basically consistent with the thin carbon layer comparison ratio.
[0077] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described or recorded in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0078] The embodiments described above are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application, and should all be included in the protection scope of the present application.
Claims
1. A method for preparing a lithium iron phosphate carbon-coated material, characterized in that: The steps include: S1, mixing a lithium source, a phosphorus source, an iron source and a primary carbon source, and adding water to prepare a first mixed slurry; S2, grinding the first mixed slurry to obtain a second mixed slurry; S3, drying, sintering, cooling, and crushing the second mixed slurry to obtain a primary coated lithium iron phosphate powder; S4, grinding the primary coated lithium iron phosphate powder, introducing acetylene for secondary sintering, and cooling to obtain a secondary coated lithium iron phosphate carbon-coated material.
2. The preparation method according to claim 1, characterized in that: The lithium source is a combination of one or more of lithium carbonate, lithium hydroxide, lithium oxalate, lithium acetate, lithium nitrate, lithium phosphate and lithium dihydrogen phosphate. The phosphorus source is one or more of diammonium phosphate, sodium phosphate, potassium phosphate, triammonium phosphate, diammonium phosphate, diammonium hydrogen phosphate, iron phosphate, manganese phosphate, lithium phosphate, lithium dihydrogen phosphate or phosphoric acid. The iron source is one or more of ferrous phosphate, ferrous oxide, ferrous sulfate, ferrous nitrate, ferric nitrate, ferrous chloride, ferric sulfate, ferric chloride, ferrous oxalate or ferric hydroxide. The carbon source is a combination of one or more of PEG, glucose, sucrose, citric acid, maltose, cyclodextrin, fructose and graphene.
3. The preparation method according to claim 1, characterized in that: The addition ratio of Li, P, Fe and C in S1 is 1-1.1:1:1-1.1, and the solid content of the first mixed slurry is 20%-50%.
4. The preparation method according to claim 1, characterized in that: The size of the zirconium beads used in the grinding in S2 is 0.4 μm, the grinding time is 30-180 min, and the D50 of the second mixed slurry is 0.4-0.5 μm.
5. The preparation method according to claim 1, characterized in that: The sintering process described in S3 is: nitrogen is introduced throughout the process for protection, the sintering temperature is 750-850°C, the heating rate is 5-15°C / min, and the insulation time is 8-12h.
6. The preparation method according to claim 1, characterized in that: The secondary sintering process described in S4 is: in a rotary furnace, nitrogen is passed for 0-1h before heating, and nitrogen is passed throughout the sintering process for protection. After the temperature is raised to 750°C, acetylene is passed at a flow rate of 0-0.2L / min and the temperature is kept for 0.5-1h.
7. A lithium iron phosphate carbon-coated material prepared by the method according to any one of claims 1 to 6.
8. A battery, characterized in that: It comprises the lithium iron phosphate carbon-coated material prepared by any method of claims 1-6, or the lithium iron phosphate carbon-coated material according to claim 7.
Citation Information
Cited By
High-interface-compatibility lithium iron phosphate positive electrode material, preparation method thereof and lithium battery
CN120727819A